2019
DOI: 10.1002/cam4.2109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serious mental illness on the treatment and mortality of older patients with locoregional high‐grade (nonmetastatic) prostate cancer: retrospective cohort analysis of 49 985 SEER‐Medicare patients diagnosed between 2006 and 2013

Abstract: Background The influence of serious mental illness (SMI) on the treatment and survival of patients with high‐grade prostate cancer is not well understood. We compared the initial cancer treatment and cancer‐specific mortality of SEER‐Medicare patients with locoregional high‐grade (nonmetastatic) prostate cancer with and without preexisting SMI. Methods We identified SEER‐Medicare patients who were 67 years of age or older diagnosed between 2006 and 2013 with locoregiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…This discrepancy may be explained by the diversity of sample populations and variations in both the diagnostic criteria and the specialists who made the diagnoses. Nevertheless, our result suggests that the prevalence of major psychiatric disorders among patients with degenerative thoracic or lumbar spine disease requiring surgical intervention is underestimated, perhaps because of the underdetection of psychiatric comorbidities or the relatively lower surgical rate in patients with preexisting psychiatric disorders [ 34 ]. Clinicians are advised to be aware of patients’ mental state in evaluating them for spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be explained by the diversity of sample populations and variations in both the diagnostic criteria and the specialists who made the diagnoses. Nevertheless, our result suggests that the prevalence of major psychiatric disorders among patients with degenerative thoracic or lumbar spine disease requiring surgical intervention is underestimated, perhaps because of the underdetection of psychiatric comorbidities or the relatively lower surgical rate in patients with preexisting psychiatric disorders [ 34 ]. Clinicians are advised to be aware of patients’ mental state in evaluating them for spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SMI was associated with higher hazard of 5-year cancer-specific death after accounting for competing risks of non-cancer death. 42 Again, in an Australian study, although the incidence of cancer was not higher than in the general population, psychiatric patients were more likely to have metastases at diagnosis and less likely to receive specialized interventions, with a greater case fatality. 43 Similar results were found in a study of 16 636 elderly women in which patients with comorbid anxiety and depression had an increased risk for diagnosis delay of ≥90 days from symptom recognition, and those with severe mental illness had an increased risk for initial treatment delay of ≥60 days from diagnosis.…”
Section: Incidence Of Cancer and Cancer Mortality In People With Smimentioning
confidence: 93%
“…With respect to prostate cancer, a study of 49 985 patients with locoregional high‐grade (nonmetastatic) cancer showed that having a SMI (bipolar disorder, schizophrenia, and other psychotic disorders) was associated with reduced odds of receiving surgery or radiation concurrent with hormone therapy as initial treatments in the year after diagnosis. Additionally, SMI was associated with higher hazard of 5‐year cancer‐specific death after accounting for competing risks of non‐cancer death 42 . Again, in an Australian study, although the incidence of cancer was not higher than in the general population, psychiatric patients were more likely to have metastases at diagnosis and less likely to receive specialized interventions, with a greater case fatality 43 .…”
Section: Incidence Of Cancer and Cancer Mortality In People With Smimentioning
confidence: 94%
“…Tuesley et al reported low frequency of prostate cancer screening among men with severe mental illness, and suggested that screening non-participation “may explain some of the mismatch between cancer incidence and mortality in people with severe mental illness” [ 40 ]. Fried et al found that serious mental illness in men with non-metastatic prostate cancer was associated with receipt of less aggressive treatment and worse cancer-specific survival [ 41 ]. In Sweden, PSA testing is performed on the individual’s own initiative and may be under-utilized by men with DUD.…”
Section: Discussionmentioning
confidence: 99%